Quantification of the effects of climatic factors and anthropogenic activities on streamflow: a systematic review - Susan Ngwira; Chitsanzo Damazio (Discover Water)
Abstract Rivers are vital natural resource to humans, providing essential ecosystem services and supporting natural processes like hydrological cycle and aquatic ecosystems. Growing population and development have increased water demand, making it a challenge for rivers to sustain Environmental Flow thereby impacting the resource’s sustainability. Research interest in identifying and quantifying contributions of climatic factors and human activities on streamflow has also grown significantly in recent decades. This paper review was written to provide an overview of how the effects are analyzed, synthesize common issues found in literature, and propose suggestions for mitigating these issues in future research. The study reviewed 101 papers which were selected by following the six-step systematic review approach; Scoping, planning, identification and search, article screening, eligibility evaluation, and presentation and interpretation. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement protocol was used to confirm that the systematic review met quality standards. Three common issues were identified: the indirect effects of variables were not quantified; Land Use and Land Cover was frequently used to represent human activities in the catchment; and methods used to quantify the effects typically involved dividing the time series into pre-change (baseline) and post-change (impact) periods. In conclusion, while significant progress has been made in quantifying the effects of climatic and anthropogenic factors on streamflow, some important parameters have been overlooked in existing studies. Addressing these issues will improve the accuracy of catchment analyses. Therefore, this review is crucial for minimizing errors and enhancing the reliability of research findings.